Using Western Social Theory: Towards a Moral Ethnography of Islamic Boarding Schools in West Sumatra, Indonesia - Lynette Parker (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This paper aims to map various Western social theories so that they can be used in writing